One-year intensive lifestyle intervention and improvements in health-related quality of life and mental health in persons with type 2 diabetes: a secondary analysis of the U-TURN randomized controlled trial - Allan Vaag; Mathias Ried-Larsen; Daniel E Lieberman; Bente Klarlund Pedersen; Christopher Scott MacDonald; Sabrina M Nielsen; Jakob Bjørner; Mette Y Johansen; Henning Langberg (BMJ Open Diabetes Research & Care)
Introduction The effects of lifestyle interventions in persons with type 2 diabetes (T2D) on health-related quality of life (HRQoL) and subjective well-being are ambiguous, and no studies have explored the effect of exercise interventions that meet or exceed current recommended exercise levels. We investigated whether a 1-year intensive lifestyle intervention is superior in improving HRQoL compared with standard care in T2D persons.Research design and methods We performed secondary analyses of a previously conducted randomized controlled trial (April 2015 to August 2016). Persons with non-insulin-dependent T2D (duration ≤10 years) were randomized to 1-year supervised exercise and individualized dietary counseling (ie, ‘U-TURN’), or standard care. The primary HRQoL outcome was change in the 36-item Short Form Health Survey (SF-36) physical component score (PCS) from baseline to 12 months of follow-up, and a key secondary outcome was changes in the SF-36 mental component score (MCS).Results We included 98 participants (U-TURN group=64, standard care group=34) with a mean age of 54.6 years (SD 8.9). Between-group analyses at 12-month follow-up showed SF-36 PCS change of 0.8 (95% CI −0.7 to 2.3) in the U-TURN group and deterioration of 2.4 (95% CI −4.6 to −0.1) in the standard care group (difference of 3.2, 95% CI 0.5 to 5.9, p=0.02) while no changes were detected in SF-36 MCS. At 12 months, 19 participants (30%) in the U-TURN group and 6 participants (18%) in the standard care group achieved clinically significant improvement in SF-36 PCS score (adjusted risk ratio 2.6, 95% CI 1.0 to 4.5 corresponding to number needed to treat of 4, 95% CI 1.6 to infinite).Conclusion In persons with T2D diagnosed for less than 10 years, intensive lifestyle intervention improved the physical component of HRQoL, but not the mental component of HRQoL after 1 year, compared with standard care.Trial registration number NCT02417012.